Short-term air pollution and fracture admissions in Beijing - Wang, Ning; Xu, Rongrong; Luo, Feng; Cao, Renwei; Wang, Zhongyu; Chen, Shuo; Zhao, Xian; Lu, Shuai; Zha, Yejun; Wei, Yongjie; Xu, Qiujin; Li, Minjuan (Frontiers in Public Health, 2025)
IntroductionLimited evidence exists on the links between ambient air pollution and fractures. This study aimed to investigate the association between short-term exposure to criteria air pollutants and hospital admissions for fractures.MethodsWe collected daily data on six criteria air pollutants and fracture admissions from Beijing Jishuitan Hospital between June 2021 and May 2023. Generalized additive models (GAM) with quasi-Poisson regression were applied to quantify the effects of air pollutants on admissions.ResultsWe identified 16,532 records on fracture admissions. At the lag03 day, an increase of 1 μg/m3 in PM2.5 and NO₂ was significantly associated with a 0.12% (95% CI: 0.01, 0.23%) and 0.26% (95% CI: 0.01, 0.51%) increase in fracture admissions, respectively. The exposure-response curve for PM2.5 showed a sharp rise after an initial decline at lower concentrations, which may be a model artifact. Stratified analyses revealed stronger associations in the younger population and a significant association between PM2.5 exposure and fracture risk in males. PM2.5 was also significantly associated with admissions for fragility fractures.DiscussionThis study suggests that short-term exposure to air pollution, with observed cumulative lag effects, may increase the risk of fracture-related hospitalizations. These findings highlight the potential role of air pollutants as an environmental risk factor for fractures.